1982
DOI: 10.1037/0033-2909.91.3.673
|View full text |Cite
|
Sign up to set email alerts
|

Influential companions: Effects of one strategy on another in the within-subjects designs of cognitive psychology.

Abstract: Within-subjects designs have obvious advantages, but they allow asymmetric transfer from influential companion conditions to bias the results. Examples are given both where asymmetric transfer occurs and where asymmetric transfer probably occurs but is not mentioned. The object of experimenting in the laboratory is to get away from variables that bias the results in unknown ways. Using a within-subjects design puts back the variables, all neatly balanced for subjects and order, but it still biases the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 35 publications
1
82
1
Order By: Relevance
“…Order of condition, however, was not found to interact with gum condition for either stress measure. This suggests that novelty-induced asymmetric transfer (Poulton, 1982) did not occur. Notwithstanding this analysis, sessions were longer in the Scholey et al study indicating that the effects of gum on stress may be limited to more prolonged instances of stress (e.g.…”
mentioning
confidence: 91%
“…Order of condition, however, was not found to interact with gum condition for either stress measure. This suggests that novelty-induced asymmetric transfer (Poulton, 1982) did not occur. Notwithstanding this analysis, sessions were longer in the Scholey et al study indicating that the effects of gum on stress may be limited to more prolonged instances of stress (e.g.…”
mentioning
confidence: 91%
“…In most cases, the manipulationwas within subjects (blocked or randomized) and did in fact produce switch preparation. The preference for within-subjects designs is unsurprising, given their improved statistical power; nonetheless, such designs leave open the possibility that exposure to different levels of the independent variable produce carryover effects that confound interpretation of the results (Poulton, 1982). In the case of switch preparation, it is at least conceivable that, exposed to random or perhaps even blocked levels of SOA, the system will adopt compromise settings of the parameters that govern preparatory processing in such a way that the anticipated effects of the manipulation are not realized.…”
mentioning
confidence: 99%
“…The following experiment tested the claims made by Poulton (1982) and directly assessed the impact that differential transfer effects may have in research employing within-subject designs such as that reported in Kellas, Simpson, and Ferraro (1988). A portion of the present research replicated the effects found in Kellas, Simpson, and Ferraro, but manipulated task condition within subjects and varied the order in which the three tasks were performed.…”
mentioning
confidence: 78%